Draft Annual Plan Proposals 1970-71 Government of Orissa - Planning Commission (Planning Commission, 1970)
The draft Fourth Five Year plan has been formulated according to the guide lines given by the various working groups formed by the Government of India. The Annual Plan for 1969-70 is but a part of the general plan and same approach has been followed in formulating the Annual plan for 1970-71.
Government of Orissa, Planning and Coordination Department (Planning Branch)